Life in a Cambodian Orphanage : A Childhood Journey for New Opportunities - Carpenter, Kathie Lou (Book collections on Project MUSE., 2021)
"What is it like to grow up in an orphanage? What do residents themselves have to say about their experiences? Are there ways that orphanages can be designed to meet children's developmental needs and to provide them with necessities they are unable to receive in their home communities? In this book, detailed observations of children's daily life in a Cambodian orphanage are combined with follow-up interviews of the same children after they have grown and left the orphanage. Their thoughtful reflections show that the quality of care children receive is more important for their well-being than the site in which they receive it. Life in a Cambodian Orphanage situates orphanages within the social and political history of Cambodia, and shows that orphanages need not always be considered bleak sites of deprivation and despair. It suggests best practices for caring for vulnerable children regardless of the setting in which they are living"--